Companies contribute significantly to the integration of refugees in Germany - Alexander Kritikos; Maximilian Priem; Anne-Christin Winkler (DIW Weekly Report, 2022)
Following the 2015 refugee influx, recent studies have found that around one in four companies have hired refugees. A survey of 100 companies that hired refugees shows that hiring refugees can increase employee satisfaction, improve reputations, and positively affect corporate developments. At the same time, hiring refugees also poses challenges for employers. These include barriers in the hiring process, poor language skills, and their foreign qualifications not being recognized. To solve these problems, firms use both public and private support instruments alongside internal measures. While integrating refugees into the workplace using these instruments has been successful, the potential of self-employment remains untapped: refugees launch new businesses much less often in Germany than in their countries of origin. Accordingly, there should be an increased focus on measures supporting refugees interested in self-employment.
Keywords: F22; J15; E24; 330; migration; labor market integration; integration programs; survey